Mutu Pendidikan Sekolah Dasar di Daerah Diseminasi Primary Education Quality Improvement Project (PEQIP) - A. Supriyanto (Universitas Negeri Malang, 2016)
The purpose of this study was to describe information about educatioanl quality of Primary Schools (SD) supported or developed by the Primary Education Quality Improvement Project (PEQIP) in Indonesia. The study was held in 90 Primary Schools from 6 Provinces. Data were collected by an educational quality assesment instrument and analysed statistically in central tendency (mean) measures. It was found that educational quality of Primary Schools developed by the Primary Education Quality Improvement Project (PEQIP) fell into good category, especially in those aspects as school leardership, school environment, school finace, learning-teaching process, school organization, and personnel attendance